Beinoni - Lowe, Mari (Levine Querido, 2025)
"In a Beinoni time there should be no war, no terrible illness, no crime. Even if that also means there won't be any great discoveries, any cures, anything extraordinary. Ezra believes that's worth fighting for. In fact, he's been training most of his life to fight a battle to determine whether Beinoni time continues, or gives way to a more violent, less certain future. He is the Nivchar, the chosen one, with the sign of the scales on his skin. When he comes of age at his bar mitzvah, so too will the gurya, a fiery beast of uncertain form, emerging from a cave to conquer, destroy, and herald a time of conflict. But Ezra begins to sense that something is very wrong. His friends, his neighbors, the whole world is losing the careful, even balance he's come to expect in a Beinoni time. It was always uncertain whether he'd be able to best his terrifying, magical foe. But now, is it even possible?" --